Large-Disturbance Instability Modes of Power System with Synchronous Generator and VSC Interfaced Generation - Liangshuai Hao; Lei Chen; Yong Min; Yalou Li; Shiyun Xu (CSEE Journal of Power and Energy Systems)
It is essential to study large-disturbance stability of power systems with high proportion of power electronic devices to discover new instability modes of renewable energy generation connected to the grid. In this paper, a model of power system with synchronous generator (SG) and voltage source converter (VSC) interfaced wind power generation is built, and time-domain simulations of the system under large disturbances are carried out for two cases in which the proportion of wind power is small and large, respectively. When wind power takes up a small proportion, instability mode of the system is rotor angle instability dominated by the SG. When wind power takes up a large proportion, instability is caused by outer control loop. The mechanism of new instability mode introduced in the wind power control link is analyzed from the angle of voltage limit and power limit. In addition, this paper studies the effect of low-voltage ride through (LVRT) switching strategy. Through comparison of simulations, it is verified different switching control strategies may correspond to different fault critical clearing time, i.e. different large-disturbance stability.